Advances in the chemical modification of nanocellulose for biodegradable plastics reinforcement - Zhang, Shuya; Che, Mingda; Huang, Renliang; Cui, Mei; Qi, Wei; Su, Rongxin (International Journal of Agricultural and Biological Engineering, 2025)
As non-degradable traditional plastics contribute to environmental pollution, biodegradable polymers have been identified as a promising alternative. However, inherent drawbacks such as low toughness, poor tensile strength, and reduced thermal degradation temperatures limit the further development of biodegradable polymers. Nanocellulose has the potential to enhance the properties of biodegradable polymers without compromising their biodegradability. However, the abundant hydroxyl groups in nanocellulose’s molecular chains result in poor compatibility with hydrophobic polymers, requiring surface modification prior to their combination. This review first introduces several common biodegradable polymers and three types of nanocellulose, followed by a comprehensive analysis of the recent advancements in the chemical modification methods of nanocellulose over the last five years. These methods encompass esterification, oxidation, silylation, and graft modification. The focus of this discussion is primarily on the modification strategies, enhancement effects, and mechanisms. Furthermore, the degradability and applications of modified nanocellulose composites are summarized. Finally, the main challenges hindering the development of chemically modified nanocellulose-reinforced biodegradable polymers are proposed. It is hoped that this review will inspire future researchers to develop industrially valuable chemically modified nanocellulose-reinforced biodegradable polymers. Keywords: biodegradable polymers, nanocellulose; surface modification, reinforcement mechanisms, degradability, applicationDOI: 10.25165/j.ijabe.20251801.9479Citation: Zhang S Y, Che M D, Huang R L, Cui M, Qi W, Su R X. Advances in the chemical modification of nanocellulose for biodegradable plastics reinforcement. Int J Agric & Biol Eng, 2025; 18(1): 10–24.